2004
DOI: 10.1111/j.1538-7836.2004.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of combination chemotherapy with and without low‐molecular‐weight heparin in small cell lung cancer

Abstract: Summary. Background Small cell lung cancer (SCLC) is a chemotherapy-responsive tumor type but most patients ultimately experience disease progression. SCLC is associated with alterations in the coagulation system. The present randomized clinical trial (RCT) was designed to determine whether addition of low-molecular-weight heparin (LMWH) to combination chemotherapy (CT) would improve SCLC outcome compared with CT alone. Methods Combination CT consisted of cyclophosphamide, epirubicine and vincristine (CEV) giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
293
3
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(310 citation statements)
references
References 17 publications
11
293
3
3
Order By: Relevance
“…Low molecular weight heparin (LMWH) may attenuate these events through multiple mechanisms, including 1) by directly inhibiting thrombin or other coagulation proteins by catalyzing antithrombin, 3 2) by indirectly inhibiting thrombin formation by stimulating the release of tissue factor pathway inhibitor, an effective inhibitor of TF-mediated coagulation, 3 and 3) by inhibiting VEGF-A. 3 growth in several cancers in early, 32,33 but not advanced disease. 21 We show that LMWH significantly reduced tumor cell proliferation and thrombin generation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight heparin (LMWH) may attenuate these events through multiple mechanisms, including 1) by directly inhibiting thrombin or other coagulation proteins by catalyzing antithrombin, 3 2) by indirectly inhibiting thrombin formation by stimulating the release of tissue factor pathway inhibitor, an effective inhibitor of TF-mediated coagulation, 3 and 3) by inhibiting VEGF-A. 3 growth in several cancers in early, 32,33 but not advanced disease. 21 We show that LMWH significantly reduced tumor cell proliferation and thrombin generation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This finding strongly indicates that inhibition of P-selectin is one of the main cancer inhibitory activities of heparin [91]. Based on the encouraging observations with heparin treatment evaluated in retrospective studies, several recent prospective clinical trials have been performed to study this phenomenon [92][93][94][95]. The promising results from the clinical studies, primarily in earlier stage patients together with the experimental evidence suggests that heparin treatment directly affect the metastasis rather than by simple inhibition of coagulation [35].…”
Section: Platelets As Therapeutic Targets For Anti-cancer Therapiesmentioning
confidence: 99%
“…The effect of heparin on tumors includes interference with cancer-induced hypercoagulation, cancer cell proliferation, degradation of the extra-cellular matrix (involving the heparan sulfate chains of cell surface and extracellular matrix proteoglycans), angiogenesis, selectin-mediated binding of platelets and cancer cells, growth factors and their receptors, hepara- nase, tumor progression, and metastasis [13,14] . Heparin was proposed to have a role in maintaining the effects of chemotherapeutic drugs, as both UFH and LMWH have been shown to act as chemotherapy sensitizers [4,5] . In our evaluation of the influence of heparin on tumor cell proliferation, cell cycle and apoptosis, we found that it could inhibit proliferation of PC-3M tumor cells and arrest them in the G 0 /G 1 phase.…”
Section: Effect Of Heparin On Brdu Incorporation and Ki67 Expression mentioning
confidence: 99%
“…Two trials (FAMOUS and MALT) previously studied the effect of unfractionated heparin (UFH) [4] or low molecular weight heparin (LMWH) [5] in patients with small cell lung cancer. In both of these studies, a statistically significant survival advantage was observed in patients randomized to chemotherapy plus UFH or LMWH relative to patients who received chemotherapy alone.…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 99%